2013
DOI: 10.1074/jbc.m113.512962
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Speckle-type POZ Protein (Spop) by Daz Interacting Protein 1 (Dzip1) Is Essential for Gli Turnover and the Proper Output of Hedgehog Signaling

Abstract: Background: Although Dzip1 positively influences Hedgehog signaling by regulating ciliogenesis, it inhibits the Hedgehog pathway through an unclear mechanism. Results: Dzip1 knockdown destabilizes Spop E3 ubiquitin ligase, leading to increased Gli transcription factor levels and phenotypes resembling Hedgehog signaling activation. Conclusion: Dzip1 inhibits Hedgehog signaling through stabilizing Spop. Significance: We uncover a novel Gli regulatory mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 63 publications
0
18
1
Order By: Relevance
“…Recent studies using cultured mammalian cells or mRNA injection in Xenopus eggs also suggested a negative role of Spop in Hh signaling (18)(19)(20)(21)24). It is worth noting that a key difference between these studies and our in vivo data lies in the roles of Spop in the regulation of Gli2, the primary activator of the mammalian Hh pathway.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Recent studies using cultured mammalian cells or mRNA injection in Xenopus eggs also suggested a negative role of Spop in Hh signaling (18)(19)(20)(21)24). It is worth noting that a key difference between these studies and our in vivo data lies in the roles of Spop in the regulation of Gli2, the primary activator of the mammalian Hh pathway.…”
Section: Discussioncontrasting
confidence: 51%
“…The Spop homolog in Drosophila, known as hib or rdx, also mediates the degradation of Ci, the sole Gli family member in flies, and inhibits Hh signaling (22,23). Overexpression of Spop in Xenopus similarly reduces Hh pathway activation (24). An Spop mutant mouse strain was analyzed previously, but defects only in endocrine pancreas were reported (25).…”
mentioning
confidence: 99%
“…Interestingly, 73% of injected embryos had bodies that were bent toward the injected side, which was likely to be due to a shortened A/P axis on the injected side. Coinjection of Gli1 morpholino (Nguyen et al, 2005;Schwend et al, 2013) clearly rescued the Rusc1 knockdown phenotypes, with the majority of embryos (96%, n=45) developing a straight body axis and only 16% of embryos showing mildly affected eyes (Fig. 8F).…”
Section: Rusc1 Inhibits Hh Signaling During Xenopus Embryonic Developmentioning
confidence: 99%
“…To determine if Rusc1 inhibits Hh signaling during development, we took advantage of the animal cap assay, which is an in vitro assay for studying Hh signaling in Xenopus embryonic tissues (Rorick et al, 2007;Min et al, 2011;Schwend et al, 2013). In Chordin (Chd) neuralized animal caps, injection of R1-MO caused a 2-fold increase in the expression of gli1, ptc2 and hhip at stage 22 and a modest increase in the expression of ptc1 (Fig.…”
Section: Rusc1 Inhibits Hh Signaling During Xenopus Embryonic Developmentioning
confidence: 99%
See 1 more Smart Citation